Semaglutide – a long – awaited cure for obesity or an elusive treatment? - Oleksak, Izabela; Maliszewska, Karolina; Szawłoga, Tomasz; Welian-Polus, Iwona; Wilanowska, Wiktoria; Babkiewicz-Jahn, Kamila; Matuszewska, Justyna; Szymańska, Adrianna (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Obesity is a challenging disease that affects various organs and cannot be easily treated. Therefore, the discovery that taking semaglutide results in weight loss caused great excitement amongst patients and medical professionals. The aim of this literature review is to explore the benefits and dangers of semaglutide and its effectiveness in treating obesity. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. Review of articles published in PubMed since 2017 until first quarter of 2024. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Analysis of literature. Obesity is an increasing problem of the world population. There are different approaches in obesity treatment. Semaglutide seems effective in treating diabetes, as well as conditions that emerge from long-lasting obesity. It showed positive influence regarding diabetic neuropathy, cardiovascular risk and more. It is important to remember about possible adverse events. The most prominent are gastrointestinal symptoms, such as nausea, diarrhea, vomiting, and abdominal pain. New reports show complications with simultaneous use of anesthesia or coexisting depression. Larger studies on semaglutiderelated side effects will be published in 2025 and in 2026. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Semaglutide is an anti-diabetic drug showing promising effects in treating diabetes and in alleviating conditions caused by obesity. It is worth remembering that its side effects have not yet been fully investigated.